Penerapan Algoritma Unary Coding Pada Aplikasi Kompresi Short Message Service (SMS) - Mesiria Sitorus (Journal of Computer System and Informatics (JoSYC), 2020)
Communication is an effort between human messages, the form of information delivered in various ways, namely with the form of sound, and text digitally. Therefore, the more information obtained digitally, it will require a very large text storage media. Short Message Service (SMS) is a facility of GSM (Global System for Mobile) technology to send and receive short messages in the form of text through mobile devices. The sender and recipient of the SMS need not be connected to each other when exchanging SMS messages. Text SMS compression can be done by several methods such as Unary Coding. Unary Coding is a type of lossless compression, and Unary Coding has been widely used data compression and is widely used with a combination of several modification techniques. In Unary Coding, compression is done by knowing the frequency of each symbol on a string. Then the frequency will be sorted by descending order. The acquisition of n for each symbol obtained from the descending order numbering is then encoded with n-1 bit 1 followed by one bit 0.